KARAKTERISTIK PERUSAHAAN DAN NILAI PERUSAHAANPADA PERUSAHAAN YANG MENGIKUTI CGPI AWARD TAHUN 2011-2016 - Samsul Rosadi; Fahri Ali Ahzar (INVENTORY: JURNAL AKUNTANSI, 2019)
This study discusses about companies that want to earn Earnings Per Share in Companies that Participate in the 2011-2016 CGPI Award. The characteristics of the company in this study are represented by company size, old company, old list, and leverage. The results of the F test show all simultaneous all independent variables on Earnings per Share. Based on the results of the test it can be concluded that the company is positive for Earning Per Share, while leverage has a negative effect on earnings per share. Old company and listing variables do not affect Earning per Share.